THE FREQUENCY AND NATURE OF ACUTE NEUROTIC DISORDERS IN PATIENTS WITH DIFFERENT LEVELS OF CARDIOVASCULAR RISK - Panchenko, M.S. (World of Medicine and Biology, 2014)
The frequency and kind of clinical forms of AND in patients with different levels of CVR were defined, and the highest frequency of neurasthenia (p < 0.01) in patients with high level of CVR in comparison with other clinical variants was proved. It was proved, that the frequency of ANDC in different groups of patients ranged from (6,1 ± 2,4)% to (23,7 ± 4,01)% and was significantly (p ≤ 0,05) higher among patients with high CVR, than in other comparison groups.
Keywords: cardiovascular risk; nonpsychotic disorders; medical and psychological support